Isolation and identification of umami‐flavored peptides from Leccinum extremiorientale and their taste characteristic. Issue 3 (28th January 2021) - Liang, Jiaming; Chen, Lili; Li, Ya‐nan; Hu, Xujia
Abstract: Umami, as one of the five basic tastes, is important to the taste of food. In this study, gel filtration chromatography and reversed‐phase high‐performance liquid chromatography were used to isolate and purify Leccinum extremiorientale cooked at high temperature. Sensory evaluation and taste dilution analysis were used to identify the most umami component in L. extremiorientale . Most umami components were determined by LC‐MS/MS. Three umami peptides were identified, and they were Asp‐Gln‐Glu‐Asp‐Leu‐Asp‐Glu‐Ser‐Leu‐Ile‐Gly‐Val‐Lys (DQEDLDESLIGVK), Phe‐Asn‐Glu‐Ile‐Ile‐Lys‐Glu‐Thr‐Ser‐Thr (FNEIIKETST), Tyr‐Asn‐Glu‐Tyr‐Pro‐Pro‐Leu‐Gly‐Arg (YNEYPPLGR). As far as we know, this is the first time that umami peptides have been extracted from Boletus. This study can provide a basis for the development of delicious food with Boletus characteristics. Novelty impact statement: Three umami peptides were isolated and purified from Leccinum extremiorientale for the first time. The structure characteristics of the umami peptides were analyzed according to the sequence. The results can provide practical application for the food industry.